Two Computational Strategies for the Approximate Solution of the Nonlinear Gas Dynamic Equations - Muhammad Nadeem; Mouad M. H. Ali (Journal of Mathematics)
In this article, we propose an idea of Sawi homotopy perturbation transform method (SHPTM) to derive the analytical results of nonlinear gas dynamic (GD) equations. The implementation of this numerical scheme is straightforward and produces the results directly without any assumptions and hypothesis in the recurrence relation. Sawi transform (ST) has an advantage of reducing the computational work and the error of estimated results towards the precise solution. The results obtained with this approach are in the shape of an iteration that converges to the precise solution very gradually. We provide the validity and accuracy of this scheme with the help of illustrated examples and their graphical results. This scheme has shown to be the simplest approach for achieving the analytical results of nonlinear problems in science and engineering.